Inisiasi Sekolah Keluarga dalam Pengasuhan Era Industri 4.0 di Kabupaten Jombang Jawa Timur - Widi Asih Nurhajati; Eva Iriani (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2020)
Industrial Era 4.0. brings changes in every joint of human life with the advancement of digital media. Technological development not only has a positive influence but also has implications for negative impacts on children which causes a reduction in children's cognitive and social abilities. One way to reduce this impact is to implement parenting care based on the application of 8 family functions. The initiation of a family school in Jombang is an initiative to provide understanding and skills so that parents can build their families. Sixteen material in a family school is expected to create a quality family and contribute to the realization of family resilience.